(untitled) (International Journal of Engineering and Computer Science, 2017)
Adaptive channel equalization accomplished without a training sequence is known as blind equalization. The decision directed algorithm (DDA), Godard algorithm (GA), Sato algorithm (SA), Benveniste and Goursat algorithm (BGA), and the stop–and-go algorithm (SNGA), are examples of Blind equalization techniques. These algorithms exhibit very slow convergence rates when compared to algorithms employed in conventional data equalization schemes. In order to speed up their convergence process, a modified algorithm (MA) can be employed which uses a combination of DDA and GA. The modified algorithm has demonstrated their effectiveness compared to other conventional techniques especially in the noisy environment.